Anti-melanoma effects of S-allyl-L-cystine sulfoxide (ACSO/alliin) from garlic in C57BL/6J mice - Yusuke Yamaguchi; Toshiki Ando; Tomoaki Yazaki; Hitomi Kumagai (Journal of Functional Foods, 2023)
Certain foods modify the risk of developing melanoma. Various garlic compounds, including odor precursors and their derivatives, inhibit tumor growth; thus, garlic could protect against melanoma. However, it is unclear if S-allyl-L-cystine sulfoxide (ACSO/alliin), which is the most abundant (>10 mg/g) odor precursor in fresh raw garlic, has anti-melanoma effect. We investigated if ACSO and the related compounds suppress tumor growth in vivo and in vitro. We orally administered ACSO, S-methyl-L-cystine sulfoxide (MCSO), and S-allyl-L-cystine (ACS) to mice with xenografted melanoma and observed the effect of these administrations on tumor size and lactate dehydrogenase activity. The effect of ACSO, MCSO, and ACS on B16F1 melanoma cells viability was also studied. We found that only ACSO suppressed tumor growth in vivo and in vitro. In addition, the sera collected from rats after oral administration of ACSO suppressed melanoma proliferation in vitro. ACSO may be the key anti-melanoma compound in garlic.